Visual Basic 2005 : a developer's notebook - MacDonald, Matthew (Developer's notebook series., 2005)
To bring you up to speed with Visual Basic 2005, this practical book offers nearly 50 hands-on projects. Each one explores a new feature of the language, with emphasis on changes that can increase productivity, simplify programming tasks, and help you add new functionality to your applications. You get the goods straight from the masters in an informal, code-intensive style.